Recent insights and advances in gut microbiota's influence on host antiviral immunity - Liu, Ying; Yan, Danying; Chen, Ran; Zhang, Yingying; Wang, Chuwen; Qian, Guoqing (Frontiers in Microbiology, 2025)
A diverse array of microbial organisms colonizes the human body, collectively known as symbiotic microbial communities. Among the various pathogen infections that hosts encounter, viral infections represent one of the most significant public health challenges worldwide. The gut microbiota is considered an important biological barrier against viral infections and may serve as a promising target for adjuvant antiviral therapy. However, the potential impact of symbiotic microbiota on viral infection remains relatively understudied. In this review, we discuss the specific regulatory mechanisms of gut microbiota in antiviral immunity, highlighting recent advances in how gut microbiota regulate the host immune response, produce immune-related molecules, and enhance the host's defense against viruses. Finally, we also discuss the antiviral potential of oral probiotics.